Distinct infant feeding type-specific plasma metabolites at age 3 months associate with body composition at 2 years. Issue 6 (June 2022) - van Beijsterveldt, Inge A.L.P.; Myers, Pernille Neve; Snowden, Stuart G.; Ong, Ken K.; Brix, Susanne; Hokken-Koelega, Anita C.S.; Koulman, Albert
Summary: Background & objectives: Early life is a critical window for adiposity programming and metabolic profile may affect this programming. We investigated if plasma metabolites at age 3 months were associated with fat mass, fat free mass and abdominal subcutaneous and visceral fat outcomes at age 2 years in a cohort of healthy infants and if these associations were different between infants receiving exclusive breastfeeding (EBF) and those with exclusive formula feeding (EFF). Methods: In 318 healthy term-born infants, we determined body composition by Dual Energy X-ray absorptiometry (DXA) and visceral fat by abdominal ultrasound at 2 age years. High-throughput metabolic profiling was performed on blood samples collected at age 3 months. Tertiles were generated for each body composition outcome and differences in plasma metabolite levels at age 3 months between infants with high and low body composition outcomes at age 2 years were evaluated in general, as well as separately in EBF- and EFF-infants. Results: Distinct plasma metabolite variables identified at age 3 months were associated with body composition at 2 years. These metabolites included several classes of lyso-phospholipids. Associations between the metabolites at age 3 months and fat mass index, fat mass percentage, fat free mass index and visceral fat at 2 years were predominantly found in EBF-infants. Conclusion: Associations between plasma metabolite levels at age 3 months and high body fat mass at 2 years depend on infant feeding type. These findings contribute to our insight into the importance of infant feeding on adiposity programming in early life.